2018
DOI: 10.1158/1535-7163.mct-17-1240
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Thioredoxin-Interacting Protein by a Histone Deacetylase Inhibitor, Entinostat, Is Associated with DNA Damage and Apoptosis in Esophageal Adenocarcinoma

Abstract: In 2017, an estimated 17,000 individuals were diagnosed with esophageal adenocarcinoma (EAC) and less than 20% will survive 5 years. PET-avidity is indicative of high glucose utilization and is nearly universal in EAC. TXNIP blocks glucose uptake and exhibits pro-apoptotic functions. Higher expression in EAC has been associated with improved disease-specific survival, lack of lymph node involvement, reduced perineural invasion, and increased tumor differentiation. We hypothesized that TXNIP may act as a tumor … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…TXNIP is expressed at a lower level in various cancers (such as liver, breast and bladder cancer) and is a multifunctional protein that controls various cellular processes, such as cell proliferation, apoptotic signaling, oxidative stress and inflammation [44][45][46][47]. Consistent with the findings that overexpression of TXNIP promotes DNA damage in esophageal adenocarcinoma [48], senescence in vascular endothelial cells [49], we demonstrated that TXNIP, may function downstream of PRMT5 to regulate DNA damage signaling and p21-mediated cellular senescence in U2 OS cells. Surprisingly, similar to that of p21 regulation, we also found that knockdown of PRMT5 only upregulated the protein but not the mRNA level of TXNIP.…”
Section: Discussionsupporting
confidence: 72%
“…TXNIP is expressed at a lower level in various cancers (such as liver, breast and bladder cancer) and is a multifunctional protein that controls various cellular processes, such as cell proliferation, apoptotic signaling, oxidative stress and inflammation [44][45][46][47]. Consistent with the findings that overexpression of TXNIP promotes DNA damage in esophageal adenocarcinoma [48], senescence in vascular endothelial cells [49], we demonstrated that TXNIP, may function downstream of PRMT5 to regulate DNA damage signaling and p21-mediated cellular senescence in U2 OS cells. Surprisingly, similar to that of p21 regulation, we also found that knockdown of PRMT5 only upregulated the protein but not the mRNA level of TXNIP.…”
Section: Discussionsupporting
confidence: 72%
“…Elevated levels of Trx system proteins (Trx-1, TrxR-1, Trx-2, and TrxR-2) and decreased levels of TNXIP protein are involved in various cancers [ 137 140 ]. A similar phenomenon was discovered in oral cancers [ 141 143 ] and esophageal adenocarcinoma [ 144 ]. Moreover, Kaplan-Meier's analysis revealed that the expression level of Trx was significantly related with a lower 5-year survival rate in patients with tongue squamous cell carcinoma [ 141 ].…”
Section: Modulate Ros Generation and Elimination To Improve The Efsupporting
confidence: 76%
“…Despite great efforts to improve the treatment of esophageal adenocarcinoma, its 5-year survival rate is still <20% (88,89). In EAC, TXNIP has been confirmed to be an independent prognostic factor for distant metastasis-free survival (90). Studies have indicated that TXNIP overexpression can decrease tumor growth in mice.…”
Section: Txnip and Gastroesophageal Cancermentioning
confidence: 99%